Impact of Crowded Sky on GNSS Positioning - Shamal Fatah Ahmed (Polytechnic Journal)
Presently, there is a huge number of Global Navigation Satellite System (GNSS) satellites in orbit, and it is possible for users to have a clear view with a high number of satellites at a single epoch. This large number of satellites results in a significant improvement in satellite geometry, visibility, Dilution of Precision (DOP), and simultaneously, reduction of occupation time and sufficient time to fix the integer ambiguity. The static method is the most accurate method to establish geodetic networks using satellites, but the length of time required for the survey and the post-processing of the data may restrict its applicability. This paper investigated the impact of increasing number of satellites, regardless the type of the system, on occupation time and evaluating accuracy in static method with a 13 km baseline length. The observations were assessed and compared to the accuracy obtained from different satellite numbers in different periods. The results indicate that by increasing satellite’s number from 4 to 20, the occupation time reduces by 83% from 30 min. to 5 min., and position dilution of precision (PDOP) reduces from 5.30 to 1.4